BRAND IDENTIFICATION, SATISFACTION, BRAND TRUST, DAN COMMITMENT TERHADAP CUSTOMER LOYALTY PADA KONSUMEN MOTOR SPORT - DENNY SEPTA HARYANTI; EDDY HERMAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to examine and analyze the influence of customer brand identification (CBI), customer satisfaction (SAT), customer brand trust (CBT), and customer commitment (CM) to customer loyalty (CL) on Yamaha Vixion motor sport consumers in DKI Jakarta. The form of research conducted in this study are causal and descriptive. Sampling using pusposive sampling technique with the number of respondents as many as 281 respondents. The data analysis method used in this study is SEM (Structural Equation Model) with AMOS tools. The result of this study indicates that CBI, SAT, CBT, and CM had effect to CL. CBT had effect to CLmediating through SAT, CBT, and CM. Then, SAT had effect to CM mediating through CBT. CBI had effect to CBT mediating through SAT, and CBI had effect to CM mediating through SAT.